Promoting Information in the Marketplace for Financial Services: Financial Market Regulation and International Standards - Latimer, Paul (Springer, 2016)
This book provides a unique comparative and global analysis of the regulation of disclosure in financial (securities) markets. It is written by two authors who represent both the new world (Australia) and the old world (Germany). The authors present their research in the global business context, with legal and regulatory perspectives including some references from Africa, Asia, the Middle East and South America.